Outcome Measures in Cancer Rehabilitation: Pain, Function, and Symptom Assessment - Maldonado, Eduardo; Thalla, Nirguna; Nepaul, Sargoon; Wisotzky, Eric (Frontiers in Pain Research, 2021)
Assessing cancer rehabilitation outcome measures is integral for patient assessment, symptom screening and advancing scientific research. In the broad field of cancer rehabilitation, outcome measures can be cross cutting across many different branches of oncologic care. They can include clinician-reported, patient-reported, and objective measures. Specific outcome measures that apply to cancer rehabilitation can include those pertinent to pain, function, quality of life, fatigue, cognition, and many more. When used in cancer rehabilitation these outcome measures can be utilized to evaluate the effectiveness of an intervention and to triage to the appropriate supportive care service. This review article will summarize some of the commonly used outcome measures that can be used in the setting of cancer rehabilitation to support scholarly work and patient care.